Hubungan Variasi Gaya Mengajar Guru dengan Hasil Belajar Siswa Kelas V pada Pembelajaran Matematika di SD Negeri 30 Banyuasin III - Kamila, Musyafa Diya; Elhefni, Elhefni; Wibowo, Djoko Rohadi; Sudarti, Dwi Okti (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2022)
This study aims to find out how the variations in teacher teaching styles in mathematics learning in class V at SDN 30 Banyuasin III, to determine student learning outcomes in learning mathematics in class V at SDN 30 Banyuasin III, and to find out whether there is a relationship between variations in teacher teaching styles and results. student learning in class V mathematics learning at SDN 30 Banyuasin III. This research is a quantitative correlation research with data collection instruments used are questionnaires, tests and documentation. The results showed: (1) From the results of the questionnaire calculation, the overall indicator of the variation in the teaching style of the Mathematics teacher class V SDN 30 Banyuasin III was in the good category with an average score of 68. The lowest score was 55 and the highest score was 75. TSR conversion average value of 68 is included in the 2nd class interval (62 - 72), meaning that in the first problem formulation the answer is about how the variation of teacher teaching styles in learning mathematics in class V at SD Negeri 30 Banyuasin III is categorized as moderate. (2) From the results of the test calculations, overall student learning outcomes in Mathematics learning class V at SDN 30 Banyuasin III are in the good category with an average score of 73. The lowest score is 65 and the highest score is 80. Based on the TSR conversion, the average value is obtained. The average of 73 is included in the 2nd class interval (68 - 77), meaning that in the first problem formulation, the answer is how the variations in teacher teaching styles in learning mathematics in class V at SD Negeri 30 Banyuasin III are categorized as moderate. (3) Is there a relationship between variations in the teaching style of teachers and the learning outcomes of fifth grade students in learning mathematics at SDN 30 Banyuasin III. Based on the results of calculations that have been carried out using product moment correlation analysis manually and the SPSS 1.6 application, it is known that sig. of 0.000 <0.05, meaning that it can be concluded that there is a positive and significant relationship between the two variables with rcount 0.622 (strong category) > rtable 0.344 and contribute 38.6%, it can be concluded based on the significance that Ho is rejected Ha is accepted, meaning that there is a relationship between variations in teacher teaching styles and the learning outcomes of fifth grade students in learning mathematics at SD Negeri 30 Banyuasin III.